2017
DOI: 10.1242/jcs.197004
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ciliary retrograde protein trafficking by the Joubert syndrome proteins ARL13B and INPP5E

Abstract: ARL13B (a small GTPase) and INPP5E (a phosphoinositide 5-phosphatase) are ciliary proteins encoded by causative genes of Joubert syndrome. We here showed, by taking advantage of a visible immunoprecipitation assay, that ARL13B interacts with the IFT46-IFT56 (IFT56 is also known as TTC26) dimer of the intraflagellar transport (IFT)-B complex, which mediates anterograde ciliary protein trafficking. However, the ciliary localization of ARL13B was found to be independent of its interaction with IFT-B, but dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
101
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(112 citation statements)
references
References 60 publications
11
101
0
Order By: Relevance
“…Previous studies have shown that Arl13b loss leads to aberrant SMO accumulation in cilia, suggesting that Arl13b limits the ciliary accumulation of SMO, possibly by promoting its ciliary export . We wondered, therefore, whether elevated ciliary ARL13B levels in RAB35‐depleted cells are required for the SMO localisation defect in these cells.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies have shown that Arl13b loss leads to aberrant SMO accumulation in cilia, suggesting that Arl13b limits the ciliary accumulation of SMO, possibly by promoting its ciliary export . We wondered, therefore, whether elevated ciliary ARL13B levels in RAB35‐depleted cells are required for the SMO localisation defect in these cells.…”
Section: Resultsmentioning
confidence: 94%
“…Arl13b consists of an N‐terminal guanine nucleotide‐binding (G) domain and an unusually long C‐terminal tail with coiled coil (CC) and proline‐rich (PR) domains (Fig B) . All these domains were previously shown to be important for protein–protein interactions; for example, IFT‐B proteins interact with Arl13b via its PR domain, while INPP5E binds to the G‐domain . Arl13b also contains a C‐terminal RVEP motif for ciliary targeting and N‐terminal palmitoylation for ciliary membrane anchoring .…”
Section: Resultsmentioning
confidence: 99%
“…Expression vectors for the IFT-B subunits were described previously (Katoh et al. , 2016; Nozaki et al. , 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The cell lysates were immunoprecipitated with GST–anti-GFP Nb prebound to glutathione–Sepharose 4B beads, and bound proteins were subjected to SDS–PAGE and immunoblotting analysis using anti-HA, anti-mRFP, anti-tRFP, or anti-GFP antibodies as described previously (Katoh et al. , 2015, 2016; Nozaki et al. , 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Defects in the IFT components have been shown to cause a spectrum of diseases, ranging from developmental defects to obesity, diabetes, and cancer. Many of these diseases, or ciliopathies, manifest as genetic syndromes, such as Joubert syndrome, Bardet-Biedel (BBS), Meckel-Gruber (MKS), and Nephronophthisis (NPHP)(Barker et al, 2014; Nozaki et al, 2017; Srivastava and Sayer, 2014; Su et al, 2014; Suspitsin and Imyanitov, 2016). …”
Section: Introductionmentioning
confidence: 99%